The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/1082013209350352
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic and Conventional Heating of Pomegranate Juice: Effects on Rheology, Color, and Total Phenolics

Abstract: Ohmic heating is an alternative fast-heating method especially for liquid foods. In this study, pomegranate juice samples, prepared by two different extraction methods, were heated ohmically by matching the same thermal history, with that of the conventional method. The ohmic heating application was conducted by changing the voltage gradient (10—40 V/cm) at 50 Hz. The samples were heated from 20 ° C to 90°C and held at 90 °C for different treatment times (0, 3, 6, 9 or 12 min). Although rheological properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 53 publications
4
50
1
4
Order By: Relevance
“…Fewer studies have been conducted on the use of novel thermal processing methods on exotic fruits, and Yildiz, Bozkurt, and Icier (2009) demonstrated that ohmic heating did not cause any different effect in other quality indices and total phenolic contents of pomegranate juice than the conventional heating.…”
Section: Novel Thermal Processing Techniquesmentioning
confidence: 99%
“…Fewer studies have been conducted on the use of novel thermal processing methods on exotic fruits, and Yildiz, Bozkurt, and Icier (2009) demonstrated that ohmic heating did not cause any different effect in other quality indices and total phenolic contents of pomegranate juice than the conventional heating.…”
Section: Novel Thermal Processing Techniquesmentioning
confidence: 99%
“…If whole fruits are pressed to prepare fresh juices (this is not the case of the current study, in which juices were prepared only using arils), it would be expected a large amount of bioactive compounds from the peels and consequently fresh juices would have high antioxidant capacity. Likewise, processing and pasteurization conditions play an important role in the antioxidant capacity of juice, since the bioactive compounds are affected by extrinsic factors such as oxygen, light and especially temperature [25][26][27].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Researchers should be encouraged by the industry or government, and further studies should be conducted on the characterisation of all system and sample behaviour (Bozkurt and Icier, 2010b). In recent years, several researches has been conducted on the ohmic processing of meat products (Halden et al, 1990;Yongsawatdigul et al, 1995;Kim et al, 1996;Roberts et al, 1998Roberts et al, , 2002Ozkan et al, 2004;Shirsat et al, 2004a,b;Piette et al, 2004;de Halleux et al, 2005;Wills et al, 2006;McKenna et al, 2006;Gin and Farid, 2007;Liu et al, 2007;Sarang et al, 2008;Tulsiyan et al, 2008;Marra et al, 2009;Bozkurt, 2009;Icier, 2009a, 2010a,b). These studies has proved the ohmic cooking as an alternative cooking method for meat products by taking account of its faster-homogeneous heating mechanism and its effects on the some quality attributes.…”
Section: Introductionmentioning
confidence: 99%